Efektivitas Pendekatan ABA/VB dalam Meningkatkan Kemampuan Bahasa Ekspresif (Intraverbal) Anak Autisme di SDIK Makkah - Yuni Rusita Kania; Damri Damri (Pusat Pengembangan Ilmiah dan Penelitian Mahasiswa Universitas Negeri Padang, 2019)
This study aims to explain the effectiveness of the ABA / VB approach in improving expressive (intraverbal) language skills of autism children in SDIK Makkah. The subject in this study was a girl with the initials B who was 8 years old, and was diagnosed with autism. The method used in this study was Single Subject Research (SSR) with A-B-A design for 16 sessions with a single subject. The initial baseline phase (A1), namely the condition of the child before being treated consists of 4 sessions, the intervention phase (B) is the phase where the child is treated consists of 8 sessions and the second baseline (A2) is the condition after the intervention is stopped which consists of 4 sessions. Processing data is measured and analyzed using visual graphics. The results obtained are the ABA / VB approach is effective in improving expressive (intraverbal) language skills of children with autism. This is evidenced by the results of the percentage overlap namely the comparison between the initial baseline (A1) with an intervention of 0% and the comparison of the second baseline (A2) with an intervention of 37.5%.